Downstreaming of Oil And Gas From Environmental Legal Aspects in Indonesia - Tjahjani, Joejoen; Albab, Ulil; Aslamiyah, Sun'iya Zahrotul; Wulandari, Rosy Dwi (Universitas Islam Lamongan, 2024)
Abstract As one of the natural resources owned by the Indonesian state, oil and gas in its utilization process must comply with applicable regulations. Downstreaming of oil and gas has various benefits such as economic diversification, increased investment, and better environmental management. With a normative juridical type of research, this research discusses the regulation of oil and gas downstreaming and reviews of oil and gas downstreaming from the aspect of environmental law. Importance synchronization of various regulations regarding oil and gas downstreaming including policies related to the environment,both in its protection and management and in law enforcement, for the sake of sustainable development towardsIndonesian Energy Security Gold 2045 and Net Zero Emission 2060 which remains environmentally friendly.